The Effect of Profitability and Company Size on Audit Delay With Auditor Reputation as Moderation for Banking Companies - Enok Rusmanah; Alifia Putri Salimah; Arief Tri Hardiyanto (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to investigate the effect of profitability and company size on audit delay, with auditor reputation acting as a moderating variable. It utilizes secondary data from the financial statements of banking companies listed on the Indonesia Stock Exchange from 2020 until 2024. The analysis employs a verification method, using an explanatory survey as the sampling technique. Using 135 observational data points of banking companies, the study employed multiple regression analysis and moderated regression analysis. The results indicate that profitability and company size affect audit delay in banking companies both partially and simultaneously. Further, auditor reputation moderates the relationship between profitability and audit delay, but not the relationship between company size and audit delay. Hence, this study provides empirical evidence on factors that determine the audit delay, which is moderated by auditor reputation, specifically for banking companies.